TRPV4 Antagonism Prevents Mechanically Induced Myotonia. Issue 2 (22nd June 2020) - Dupont, Chris; Novak, Kevin; Denman, Kirsten; Myers, Jessica H.; Sullivan, Jeremy M.; Walker, Phillip V.; Brown, Nicklaus L.; Ladle, David R.; Bogdanik, Laurent; Lutz, Cathleen M.; A. Voss, Andrew; Sumner, Charlotte J.; et al.
Abstract : Objective: Myotonia is caused by involuntary firing of skeletal muscle action potentials and causes debilitating stiffness. Current treatments are insufficiently efficacious and associated with side effects. Myotonia can be triggered by voluntary movement (electrically induced myotonia) or percussion (mechanically induced myotonia). Whether distinct molecular mechanisms underlie these triggers is unknown. Our goal was to identify ion channels involved in mechanically induced myotonia and to evaluate block of the channels involved as a novel approach to therapy. Methods: We developed a novel system to enable study of mechanically induced myotonia using both genetic and pharmacologic mouse models of myotonia congenita. We extended ex vivo studies of excitability to in vivo studies of muscle stiffness. Results: As previous work suggests activation of transient receptor potential vanilloid 4 (TRPV4) channels by mechanical stimuli in muscle, we examined the role of this cation channel. Mechanically induced myotonia was markedly suppressed in TRPV4‐null muscles and in muscles treated with TRPV4 small molecule antagonists. The suppression of mechanically induced myotonia occurred without altering intrinsic muscle excitability, such that myotonia triggered by firing of action potentials (electrically induced myotonia) was unaffected. When injected intraperitoneally, TRPV4 antagonists lessened the severity of myotonia in vivo by approximately 80%. Interpretation: These data demonstrate that there are distinct molecular mechanisms triggering electrically induced and mechanically induced myotonia. Our data indicates that activation of TRPV4 during muscle contraction plays an important role in triggering myotonia in vivo. Elimination of mechanically induced myotonia by TRPV4 inhibition offers a new approach to treating myotonia. ANN NEUROL 2020;88:297–308.